Usporedba metoda ekstrakcije RNK za molekularnu analizu u oralnoj citologiji - Alves, Mônica Ghislaine Oliveira [UNESP]; Pérez-Sayáns, Mario; Padín-Iruegas, Maria-Elena; Reboiras-López, Maria Dolores; Suarez-Peñaranda, José Manuel; López-López, Rafael; Carta, Celina Faig Lima[UNESP]; Issa, Jaqueline Scholz; García-García, Abel; Almeida, Janete Dias [UNESP] (University of Zagreb School of Dental Medicine, 2016)
Objective of work: The aim of this study was to compare three methods of RNA extraction for molecular analysis of oral cytology to establish the best technique, considering its concentration and purity for molecular tests of oral lesions such as real-time reverse transcriptase reaction. Material and methods: The sample included exfoliative cytology from the oral cavity mucosa of patients with no visible clinical changes, using Orcellex Rovers Brushï¿½. The extraction of total RNA was performed using the following three techniques: 30 samples were extracted by Trizolï¿½ technique, 30 by the DirectzolTM RNA Miniprep system and 30 by the RNeasy mini Kit. The absorbance was measured by spectrophotometer to estimate the purity. The estimated RNA concentration was obtained by multiplying the value of A260 (ng/mL) by 40. Statistical analysis of the obtained data was performed using GraphPad Prism 5.03 software with Student t, analysis of variance and Bonferroni tests, considering p =0.05. Results: Trizolï¿½ group revealed higher average concentration, followed by Direct-zolTM and Rneasy group. It was observed that the RNA Direct-zolTM group had the highest purity, followed by RNeasy and Trizolï¿½ groups, allowing for the two ratios. Conclusion: Considering all aspects, concentration, purity and time spent in the procedures, the Direct-zolTM group showed the best results.
Comparison of rna extraction methods for molecular analysis of oral cytology
Keywords: Molecular Diagnostic Techniques; Mouth Mucosa; RNA; Specimen Handling